Impact of financial instability on international crude oil volatility: New sight from a regime-switching framework. (August 2022) - Hong, Yanran; Wang, Lu; Liang, Chao; Umar, Muhammad
Abstract: In this paper, we investigate the dynamic impact of financial stress on crude oil volatility by employing a time-varying transition probabilities Markov regime-switching GARCH model (TVTP-MS-GARCH). Different from the existing work, we mainly consider the possible nonlinearity and regime changes among crude oil volatility and financial stress. First, the in-sample results strongly support the existence of the potential regime switches among the two financial fundamentals. Second, compared with the symmetric TVTP-MS-GARCH model, the model based on an asymmetric framework shows a better predictive performance in the out-of-sample findings. It implies that the dynamic impact of financial stress on crude oil exhibits an asymmetric feature. Finally, our findings are robust to several alternative checks, including other lags of financial stress and estimated window size. Thus, it is necessary to focus on the dynamic changes of financial stress for accurately predicting crude oil volatility. Highlights: This paper examines the dynamic impact of financial stress on crude oil volatility. We mainly consider the possible nonlinearity and regime changes among them. A potential regime switch exists in financial stress and crude oil volatility. We provide evidence of the asymmetric effect of financial stress on crude oil.